Mapping the Sensible Distribution, Inscription, Cinematic Thinking - Carter, Erica (Cinepoetics Essay, 2022)
Mapping figures in cinema as an experiential process inscribed within historically specific aesthetic regimes. The three long essays in this book explore mapping as a process of violent inscription on colonial landscapes (Malcomess) a practice of colonial racialisation through what Rancière terms a 'distribution of the sensible' (Carter) and a mode of culturally and historically located cinematic thinking (Rositzka).